2022
DOI: 10.3389/fvets.2021.791461
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Fecal Microflora of Wild Bar-Headed Goose in Tibet Plateau

Abstract: The bar-headed goose (Anser indicus) has two black spots on its head. It is considered an important bird in China. It breeds in plateau lakes, especially saltwater lakes, and swamp areas. However, the intestinal flora of wild bar-headed geese in the Tibet Autonomous Region is currently not known. In this study, 16S rDNA sequencing was performed on the intestinal microbes of wild bar-headed geese. A total of 513,505 reads of raw data were obtained, and the results analyzed the average number of 128,376 ± 2,392 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
(38 reference statements)
2
4
0
Order By: Relevance
“…Twenty fecal samples were used in our study, identifying 10 bacterial phyla and 9 fungal phyla. The bacterial phyla were primarily made up of Firmicutes and Proteobacteria, and this result was consistent with earlier studies on other birds, including the bar-headed goose ( Dong et al., 2021 ), Whooper Swan ( Wang et al., 2021 ), Great Bustard, Common Coot , and Common Crane ( Lu et al., 2022 ). Animals have a large distribution of Firmicutes, essential to hosts in sustaining energy metabolism ( Kaoutari et al., 2013 ) and as a gauge of fecal health ( Ley et al., 2006 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Twenty fecal samples were used in our study, identifying 10 bacterial phyla and 9 fungal phyla. The bacterial phyla were primarily made up of Firmicutes and Proteobacteria, and this result was consistent with earlier studies on other birds, including the bar-headed goose ( Dong et al., 2021 ), Whooper Swan ( Wang et al., 2021 ), Great Bustard, Common Coot , and Common Crane ( Lu et al., 2022 ). Animals have a large distribution of Firmicutes, essential to hosts in sustaining energy metabolism ( Kaoutari et al., 2013 ) and as a gauge of fecal health ( Ley et al., 2006 ).…”
Section: Discussionsupporting
confidence: 91%
“…Birds serve as a critical environmental indicator organism with their diverse genetic makeup and species diversity. The study of the composition and function of the intestinal microbiota of birds has increased exponentially in recent years due to the development of molecular biology techniques and growing interest in the bird population ( Dong et al., 2021 ; Wang et al., 2021 ). However, due to the limitations of sampling challenges and low DNA extraction amounts in field conditions, the research was primarily focused on poultry, and there were relatively few studies on the intestinal microbiota of wild birds ( Gao et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbial community composition of the two groups of mallards showed that Firmicutes, Proteobacteria, Bacteroidetes, Fusobacteria, and Actinobacteria were the dominant phyla, with an average relative abundance of more than 1%. These dominant phyla are similar to studies of gut microbiota in other wild birds, such as the Shaoxing duck (A. platyrhynchos) [36], bar-headed goose [44], whooper swan (Cygnus cygnus) [45], black-necked crane (Grus nigricollis) [46], hoatzin (Opisthocomus hoazin) [47], and turkey (Meleagris gallopavo) [48]. Firmicutes are the most prevalent and common bacterial phylum among all vertebrates.…”
Section: Discussionsupporting
confidence: 72%
“…The results showed that there was more much bile acid when the intestinal microflora was increasing in the perinatal period of Sha ling sows. Dong SX 9 used 16S rRNA sequencing on the intestinal microorganisms of wild striped goose in Tibet Autonomous Region. A total of 513,505 original data reads were obtained.…”
Section: Introductionmentioning
confidence: 99%